2012
DOI: 10.1111/j.1751-7893.2012.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and duration of untreated psychosis: a systematic review and meta‐analysis

Abstract: Earlier age at first contact and larger incidence in males support the existence of specific gender differences in first-episode psychosis; however, these are not associated with DUP length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
3
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 90 publications
7
39
3
6
Order By: Relevance
“…Males are reported to have an earlier onset of the disorder, or earlier detection of the symptoms than females (Angermeyer and Kuhn, 1988;Cascio et al, 2012). Earlier onset of schizophrenia in male patients was consistently found in Western countries (Angermeyer and Kuhn, 1988;Faraone et al, 1994;Häfner, 2003;Hambrecht et al, 1992;Szymanski et al, 1995) and in non-Western countries (Gureje, 1991;Hambrecht et al, 1992;Tang et al, 2007;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…Males are reported to have an earlier onset of the disorder, or earlier detection of the symptoms than females (Angermeyer and Kuhn, 1988;Cascio et al, 2012). Earlier onset of schizophrenia in male patients was consistently found in Western countries (Angermeyer and Kuhn, 1988;Faraone et al, 1994;Häfner, 2003;Hambrecht et al, 1992;Szymanski et al, 1995) and in non-Western countries (Gureje, 1991;Hambrecht et al, 1992;Tang et al, 2007;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…For example, men have an earlier age of disease onset, more deficit symptoms and a poorer response to antipsychotic drug treatment (Lindamer et al, 1997). Additionally, sex differences also exist regarding structural and functional brain abnormalities that may underlie the disease pathology (Cascio et al, 2012;Kulkarni et al, 2012;Gonzalez-Rodriguez et al, 2014). However, In the present study, we aimed at further characterizing the effects of prenatal LPS exposure on 5-HT 2A and mGlu2/3 receptor function in the adult rat offspring.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%
“…For example, reviews and meta-analyses have shown that men have a 1.15-1.4:1 higher incidence of schizophrenia compared to women [16][17][18][19] . Men also have an earlier age of onset compared to women across varying definitions of onset (e.g., first psychotic symptoms, first diagnosis, first hospitalization) [20,21] . Women on average have a better treatment response to antipsychotic medications compared to men, including a more rapid treatment response and lower required dose to achieve a response [12,22] .…”
Section: Introductionmentioning
confidence: 99%